Amino Acid Composition of Developing Larval Freshwater Prawn Macrobrachium rosenbergii - Roustaian, Paymon; Kamarudin, Mohd Salleh; Omar, Hishamuddin; Saad, Che Roos; Ahmad, Mansor (Wiley, 2000)
Amino acid profiles of freshwater prawn Macrobrachium rosenbergii were determined during early larval stages (I-IX) to provide some baseline biochemical information of the growing larvae. The larvae obtained from several females were stocked into three 250-L tanks at a density of 30 larvae/L. The feeding regime consisted of newly hatched Anemia nauplii and egg custard containing 5% cod liver oil. For each developmental stage, larval samples from each experimental tank were pooled, freeze dried and after acid hydrolysis, the quantification of amino acids was done by a reverse phase high performance liquid chromatography (N = 2). The highest represented of the total amino acids were for glutamic acid and phenylalanine (with cystine) with ranges from 13.4-16.6 and 9.7-11.5%, respectively, whereas tryptophan (1.4-1.6%), methionine (1.4-2.7%) and histidine (2.9-4.2%) were relatively lower. The levels of the following essential amino acids did not significantly change during larval development: arginine, leucine, phenylalanine (plus cystine), threonine, tryptophan and valine. Despite statistically significant changes that were observed in levels of some amino acids, amino acid composition appeared to be relatively unchanged during the larval growth. The results may suggest that the amino acid requirements of the freshwater prawn is relatively constant during larval life and can be satisfied by a suitable protein source that resembles the larval amino acid profile.